Nurse Educator-Led an Educational Intervention on Critical Care Nurses’ Knowledge Regarding Endotracheal Suctioning (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Studies placed a great emphasis on implementing in-service educational intervention fornurses in order to improve their knowledge regarding critical nursing procedures. Therefore, critical-carenurses need to be more knowledgeable and competent in providing patient care. Hence, the researcher(nurse educator) developed structured educational program that mainly focused on endotracheal suctioningbased on evidence-based recommended practice guidelines. Endotracheal suctioning is vitally importantnursing procedure in terms of maintaining airway patency and preventing complications. Objectives:to evaluate the effectiveness of endotracheal suctioning educational program on critical-care nurses’knowledge. Methodology: a quantitative, quasi-experimental one group pre-test and post-test design wasused. Convenience sample of 87 critical-care nurses are recruited from three hospitals at AL-Najaf ALAshraf City. The study conducted over the period of time that started on December 10, 2019 and ended onJanuary 22, 2020. Results: most of the participants had inadequate to moderate knowledge at pre-test. Whileafter implementing the educational intervention, the participants gained more knowledge and statisticalfindings indicated that all nurses have adequate knowledge regarding endotracheal suctioning. Conclusion:Endotracheal suctioning is a widely performed technique for mechanically ventilated patients in critical careunits. Nurses must be competent and well educated to perform this procedure in order to prevent patientpotential complications and achieve best outcomes. Educational intervention that led by nurse educator hasa positive influence on nurses’ knowledge. Recommendations: the researchers are highly recommendedimplementing ongoing educational program by using recent clinically recommended evidence that focuseson areas where knowledge expansion can be achieved to staff nurse. In Iraq, creating postgraduate degreefocusing on nursing education is a cornerstone to engage in the health care team and articulate new scientificapproach by using researches in the clinical setting and apply research findings in clinical practice.